Key Educational Competencies for Sustainable Development in The Cultural Life of The Baduy Community - Anggie Siti Perdani; Nur Ichsan Sumardani; Ayu Yuana (CV. Dharma Samakta Edukhatulistiwa, 2024)
This study aims to analyze the critical competencies of education for sustainable development that are available in the life of the Baduy indigenous people. The Sustainable Development Goals consist of seventeen goals and four pillars, economic, social, environmental, and law. The key competencies for sustainable development consist of thinking, anticipatory, normative, strategic, collaboration, critical thinking, self-awareness, and problem-solving competencies in integrated development. This research method is a literature study by reviewing ten sources such as newspapers, books, and articles that discuss the life of the Baduy indigenous people. This study focuses on the question How does the life of the Baduy community reflect the goals of sustainable development, especially in the social, economic, and environmental fields. The Baduy Dalam tribe is one of the ethnic groups in Indonesia who live around the Kendeng mountains (South Banten). This ethnic group still adheres to the traditions handed down from their ancestors to harmonize with the existing natural resources and origins. The key competencies of sustainable development in the cultural life of the Baduy people are expected competencies, systems thinking, collaboration, and normative. The goals of sustainable development in the cultural life of the Baduy people are about good lives and well-being, access to clean water and sanitation, cities and communities, responsible consumption and production, maintaining ecosystems, peace, peace, and strong institutions. , partnerships to achieve goals.